PENGGUNAAN RUBRIK SEBAGAI INSTRUMEN PENILAIAN DALAM KEGIATAN MENULIS TEKS EDITORIAL SISWA SEKOLAH MENENGAH ATAS [THE USE OF RUBRICS AS AN ASSESSMENT INSTRUMENT IN HIGH SCHOOL STUDENTS' EDITORIAL TEXT WRITING ACTIVITIES] - Mitra Jayanti Lase; Ernie Bertha Nababan (Universitas Pelita Harapan, 2023)
AbstractThis research is motivated by the author's findings on the structure of student editorial text opinion writing that has differences in the completeness of the content. It refers to the assessment of student achievement that is not the same assessment standard. As a series of continuous learning, this requires assessment and evaluation from the teacher. However, the unavailability of assessment instruments causes the assessment to be biased and subjective. This research was conducted on 30 class XII students at a private school in Manado. The purpose of this study is to describe the use of rubrics as a teacher's assessment instrument in writing editorial text activities for high school students. This study used the descriptive qualitative method. Based on the research results, it was found that rubrics can help teachers to see students' abilities in writing editorial texts, provide evaluations of students' writing results based on the criteria that have not been achieved, and assess students fairly and accurately based on the criteria contained in the rubric. The use of rubrics helps teachers realize God's love and justice in assessing and supporting students' potential in writing. In addition, the beauty and meaning of student writing can reveal the Creator to others. Therefore, the authors suggest determining skills that need to be assessed using rubrics, communicating achievement criteria to students, and providing evaluations based on rubrics criteria to support student growth.Bahasa Indonesia AbstrakPenelitian ini dilatarbelakangi oleh temuan penulis pada struktur tulisan opini teks editorial siswa yang memiliki perbedaan pada kelengkapan isi. Hal ini merujuk pada penilaian capaian siswa yang tidak berada pada standar penilaian yang sama. Sebagai suatu rangkaian pembelajaran yang berkelanjutan, hal ini membutuhkan penilaian dan evaluasi dari guru. Akan tetapi, tidak tersedianya instrumen penilaian menyebabkan penilaian menjadi bias dan subjektif. Penelitian ini dilakukan pada 30 siswa kelas XII di salah satu sekolah swasta di Manado. Tujuan dari penelitian ini untuk memaparkan penggunaan rubrik sebagai instrumen penilaian guru pada kegiatan menulis teks editorial siswa Sekolah Menengah Atas. Penelitian ini menggunakan metode deskriptif kualitatif. Berdasarkan hasil penelitian diperoleh bahwa rubrik dapat membantu guru melihat kemampuan siswa dalam menulis teks editorial, pemberian evaluasi pada hasil tulisan siswa berdasarkan kriteria yang masih belum tercapai, dan menilai siswa secara adil dan akurat berdasarkan kriteria yang dimuat di dalam rubrik. Penggunaan rubrik membantu guru mewujudkan kasih dan keadilan Allah dalam melakukan penilaian dan mendukung potensi siswa dalam menulis. Selain itu, keindahan dan makna tulisan siswa dapat menyatakan Pencipta kepada orang lain. Oleh sebab itu, penulis menyarankan untuk menentukan keterampilan yang perlu dinilai dari penggunaan rubrik, mengomunikasikan capaian kriteria kepada siswa, serta memberikan evaluasi berdasarkan kriteria rubrik untuk mendukung pertumbuhan siswa.